1985
DOI: 10.1002/j.1556-6676.1985.tb01095.x
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Sex Role Counseling

Abstract: The androgyny model of masculinity and femininity serves as the basis for a framework for sex role counseling applicable to both sexes. A conceptualization of individual differences in sex role-related characteristics suggests criteria for personal sex role adjustment other than universal conformity to traditional sex role requirements. It is suggested that consistency among an individual's feminine and masculine selfattributions, sex role ideals, environmental demands with their accompanying rewards and costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Another result of this analysis revealed that, during the 5-year period of 1981-1985 after the special issue, 627 articles were published. Of those, only one article written (Cook, 1985) met the analysis criteria of a 50% focus on men. However, during 1986-1990, there were 21 articles published containing the keywords, equating to 3.4% of articles.…”
Section: Jcdmentioning
confidence: 99%
“…Another result of this analysis revealed that, during the 5-year period of 1981-1985 after the special issue, 627 articles were published. Of those, only one article written (Cook, 1985) met the analysis criteria of a 50% focus on men. However, during 1986-1990, there were 21 articles published containing the keywords, equating to 3.4% of articles.…”
Section: Jcdmentioning
confidence: 99%
“…We agree that supervisors ought to take a proactive stance when it comes to gender bias against women (e.g., Gilbert, 1987b;Porter, 1985). We posit, however, that a supervisor's gender bias may adversely affect both women and men in supervision, irrespective of the supervisor's sex (Bernard & Goodyear, 1992;Cook, 1985;Gilbert, 1987aGilbert, , 1987bScher & Good. 1990;Scher, Stevens, Good, & Eichenfleld, 1987).…”
Section: Underlying Assumptionsmentioning
confidence: 99%
“…205-207). Several excellent resources currently exist that delineate a variety of exercises to increase awareness of gender related biases (see Bernard & Goodyear, 1992;Brodsky, 1980;Buhrke, 1989;Cook, 1985;Dworkin & Gutierrez, 1989;Gilbert, 1987b;Moore & Nelson, 1981;Pedersen, 1991;Vasquez, 1988; and the references therein). These exercises are particularly useful in counselor training and supervision to increase counselors' awareness of their biases and stereotypes and to integrate the cognitive knowledge gained from the readings.…”
Section: Supervisory Interventions To Reduce Gender and Cultural Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…The workshop's conceptual base encouraged participants to examine their present and past experiences with gender roles. The four major concepts of the workshop were sexism (Albee, 1981), gender role conflict (Cook, 1985;O'Neil, Helms, Gable, David, & Wrightsman, 1986;Pleck, 1981), gender role transitions (Block, 1973;O'Neil, Fishman, & Kinsella-Shaw, 1987), and the gender role journey (O'Neil, 1986). Each concept is briefly defined below to provide a theoretical context for the workshop.…”
mentioning
confidence: 99%